Human behaviour and GIS - Mario Boffi; Matteo Colleoni (Netcom)
Up to now urban mobility has been mainly measured by conventional methods and techniques, largely based on interview and self-administered survey questionnaires. The rising complexity of urban movements and their increasingly stochastic quality, compounded by new conceptualisations of mobility itself, powerfully emerging in the theoretical sociological literature, requires richer and more analytical data, and a more consistent analytical environment capable of managing the spatial dimension. The paper explores cutting-edge issues concerning methods and tools for data collection on pedestrian mobility by GPS, integrated with activity data, for the transformation of track-points into relevant time-space indicators as well as analysis of-mobility pattern inside a GIS (Geographical Information System) environment. Thematic mapping and density models will be proposed as relevant methods for visualising human behaviour in the urban space. Methodological issues will be supported by experimental data coming from a survey held in the University Campus of Milano-Bicocca and stored in SAMIT, the new research centre on spatial and environmental data.